School and Institutional Policies as Catalysts for Teacher Adaptation to Digital Learning in the New Era - Muhaimin, Mohamad; Masnawati, Eli; Hariani, Mila; Ghozali, Solchan (Journal of Social Science Studies, 2024)
Technology-based learning transformation requires teachers, especially those in the early years of their careers, to face changes in their roles that are not only technical, but also psychosocial and institutional. This study examines in depth the dynamics of novice teachers’ adaptation, coping strategies, and the influence of institutional practices and school policies in supporting the successful integration of technology in the classroom. The analysis reveals that psychological pressure and adaptation barriers often stem from individual capacity gaps and a lack of practical experience. However, the existence of a supportive pedagogical community, reflective routines, and access to digital training play a substantive role in encouraging resilience and innovation. Institutional factors, such as strengthening the digital vision, providing infrastructure, and reward systems, play an important role in creating an educational ecosystem conducive to teacher transformation. The implementation of participatory policies and data-based quality assurance strengthens the validity and accountability of educational institutions. This article emphasizes the need for simultaneous reform at the individual, institutional, and educational system levels so that digital learning can be implemented effectively, sustainably, and provide room for growth for novice teachers. Recommendations include strengthening collaboration, developing contextual training, and continuously monitoring the success of learning digitalization.